What is a child? The conception of childhood viewed primarily through the funerary culture from the Predynastic era to the Middle Kingdom - McRae, Courtney (AUC Knowledge Fountain, 2023)
This thesis uses an interdisciplinary analysis of the theories involving cultural ideas of childhood, as well as archaeological approaches to studying the funerary material culture related to children, in an attempt to determine the role of children in ancient Egypt. To achieve this, the author examines grave goods in relation to child burials from the Predynastic (5000-3200 BC) to the Middle Kingdom (2055-1650 BC) to examine the correlation between funerary material cultures with different stages of childhood. The author used these time periods in order to properly conduct an in depth analysis of early Egyptian culture. The author also analyzes changes in body containers, body positions, and burial locations that might indicate possible shifts in cultural ideas of children. The large time frame and numerous cemeteries provide context to these changes through different periods. The cemeteries used in this study are at the sites of: Abydos, Adaima, el Amrah, Badari, Ballas, Beni Hasan, Deir el Bersha, Harageh, Heliopolis, Hemamieh, Lahun, Maadi, el-Mahasna, Matmar, Mostagedda, Naga ed Der, Naqada, Qau, Tell el Dab’a (Avaris), ‘Ain Asil, Tell el Farkha, and Tell Ibrahim Awad. The author applies the archaeological theory of childhood to the research that argues: firstly, children were important members of their society; secondly, childhood is both a biological and cultural construct; and finally, children possessed material culture. The combination of funerary archaeology and childhood studies provides insights into the cultural ideas of childhood in ancient Egypt. The grave goods associated with children are analyzed to better understand what a child in ancient Egypt was in terms of cultural age, the status of children, and the concept of childhood. A comparison between sites and time periods shows differences in the quantity of grave goods, as well as body containers, hence revealing varying cultural changes in ancient Egyptian childhood over time.